Traumatic Degloving Injury of Penis And Scrotum : A Case Report - Saha, Prodyut Kumar; Rahman, Md Mizanur; Chowdhury, Md Shafiqul Alam; Rahman, Md Mostafizur; Amin, Md ATM Nurul; Bhuiyan, AKM Musa (Bangladesh Journal of Urology, 2020)
Avulsion injury of penis and scrotum are uncommon event caused by accidents and industrial machines and agricultural machine belts. Here I report the case of a 38-year old patient with avulsion and traumatic degloving of the penile and scrotal skin, with exposure of the cavernous bodies, spongy body, and testes due to an agriculture machine accident. Reconstruction was performed and achieving a satisfactory esthetic result, normal voiding and reestablished sexual function. Bangladesh Journal of Urology, Vol. 15, No. 1, Jan 2012 p.21-22